Grant Writing: Tips and Advice for New Writers - Erica Odera; Sebastian Galindo-Gonzalez; Amy Harder; Glenn D. Israel; Alexa J. Lamm (EDIS)
While grant writing is a highly useful and potentially lucrative skill, it can also be a challenge to learn how to successfully write grants. Moving through the entire process of creating and harnessing a new idea to building a collaborative team, and making sure the proposal itself is high quality and includes all the important pieces, can be daunting for new grant writers. This 5-page fact sheet shares tips and walks you through the process of writing a collaborative grant by helping illuminate how to manage the idea creation, team building, and proposal writing stages of your grant writing experience. Written by Erica Odera, Sebastian Galindo-Gonzalez, Amy Harder, Glenn D. Israel, and Alexa J. Lamm, and published by the UF Department of Agricultural Education and Communication, May 2014.